2000
DOI: 10.1046/j.1365-2362.2000.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2D6 and glutathione S‐transferase M1 genotypes and migraine

Abstract: The results of this study indicate that deficient metabolism because of mutated CYP2D6 alleles or GSTM1 allele variants is not important in the aetiology of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Negative studies evaluating candidate genes for association with migraine have included evaluation of interleukin-6 (Rainero et al 2003), DRD1, DRD3, and DRD5 , apolipoprotein E/APOE (Rainero et al 2002a), 5HT1B receptor (Maassen Van Den Brink et al 1998, inducible nitric oxide synthase/iNOS (Lea et al 2001b), cytochrome P450 2D6/CYP2D6 and glutathione S-transferase M1/GSTM1 (Mattsson et al 2000), 5-HT2A and 5-HT2B (Buchwalder et al 1996;Nyholt et al 1996;Burnet et al 1997), a nitric oxide synthase polymorphism (Nyholt et al 1996), and the DRD3 and DRD4 dopamine receptor subtypes Del Zompo et al 1998).…”
Section: Genome Scans For Familial Migrainementioning
confidence: 99%
“…Negative studies evaluating candidate genes for association with migraine have included evaluation of interleukin-6 (Rainero et al 2003), DRD1, DRD3, and DRD5 , apolipoprotein E/APOE (Rainero et al 2002a), 5HT1B receptor (Maassen Van Den Brink et al 1998, inducible nitric oxide synthase/iNOS (Lea et al 2001b), cytochrome P450 2D6/CYP2D6 and glutathione S-transferase M1/GSTM1 (Mattsson et al 2000), 5-HT2A and 5-HT2B (Buchwalder et al 1996;Nyholt et al 1996;Burnet et al 1997), a nitric oxide synthase polymorphism (Nyholt et al 1996), and the DRD3 and DRD4 dopamine receptor subtypes Del Zompo et al 1998).…”
Section: Genome Scans For Familial Migrainementioning
confidence: 99%
“…On the other hand, there were no differences between MWA and TH. Mattsson et al [16]found no association between the M1 polymorphism and migraine in a Swedish population. However, migraine patients were not classified as MWA or MWOA.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several investigations of their association with an increased risk factor for cancer [11, 12, 13, 14, 15]. However, there has only been one report regarding GST gene polymorphism and migraine [16]. We investigated the polymorphisms of GSTM1, T1 and P1 in the Japanese migraine sufferer.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the glutathione S -transferase (GST) detoxification enzymes (M1, P1 and T1) have been speculated in migraine susceptibility due to their chemical interactions with foods known to trigger migraine attacks [85] . The null genotype of the GSTM1 gene, resulting in no expression of the GSTM1 protein, was found not to be involved in a Swedish migraine cohort.…”
Section: Glutathione S-transferase Genesmentioning
confidence: 99%